“Influencia de la aplicación del programa ‘Leíto. Preparémonos para la lectura’ sobre el nivel de conciencia fonológica en niños con nivel intelectual fronterizo y con dificultades en los procesos léxicos de segundo grado de primaria de colegios públicos de la UGEL Lima 01” - Rodríguez Romero, Diana Jimena (2017)
The present research aims to determine to what extent the implementation of the program "Leito. Preparemonos para la Lectura" influences the level of phonological awareness in children of second grade of primary education with border intellectual level and difficulties in lexical processes, belonging to six public educational institutions of the UGEL LIMA 01. It is important due to its practical relevance, seeking to mitigate the difficulties that mentioned children have in learning to read; and in its theoric value, opening the way for more research to address the learning difficulties presented by the target population. It is base on what some authors expose, that border intellectual level is a metacondition of health, where a neurodevelopment disorder is present, among which the learning difficulties are, and there before deserves a specific educational attention. The present study is considered an explanatory type, and use a quasi - experimental design. A sample of 18 children was used who met the conditions of border intellectual level and difficulties in the lexical processes. They were divided into two groups, one control and one experimental, each of 9 children. The Metal linguistic Skills Test (THM) was applied to both groups. Then, the experimental group participated in the program" Leito. Preparemonos para la Lectura”; and finally both groups were retested with the THM. The results indicate that the application of the program elevates significantly the level of phonological awareness in children in the experimental group. The conclusion is that children with a border intellectual level and difficulties in lexical processes obtain improvements when they are systematically stimulated through the application of a program.